Teachers’ Perspectives on Face-To-Face English Teaching After Teaching Online In Pandemic - Asa, Muhammad Nurul (Pusat Publikasi Nusantara, 2022)
Before the pandemic, previous research found that online teaching improved teacher face-to-face teaching. Especially in Indonesia, the pandemic has provided an unsatisfactory online teaching experience. Considerably, this study aimed to investigate teachers' perception of face-to-face English teaching after online teaching in a pandemic. The study was designed as a phenomenological study with a sampling method using purposeful random sampling. Sources of data came from interviews with five teachers in urban areas and five teachers in rural areas. Data was supported by documentation and field notes. The study found that teachers perceive face-to-face English teaching practice after the pandemic has changed compared to previous face-to-face teaching. The changes can be seen from three aspects: teaching practice, teaching competencies, and impact on students.